Mast cells selectively produce inflammatory mediators and impact the early response to Chlamydia reproductive tract infection - Mayavannan, Animamalar; Shantz, Emily; Haidl, Ian D.; Wang, Jun; Marshall, Jean S. (Frontiers in Immunology, 2023)
Chlamydia trachomatis (Ct) is a Gram-negative obligate intracellular bacterium that causes reproductive tract complications in women including ectopic pregnancies and tubal factor infertility. We hypothesized that mast cells, which are common at mucosal barriers, may contribute to responses to Chlamydia infection and aimed to define human mast cell responses to Ct. Human cord blood derived mast cells (CBMCs) were exposed to Ct to assess bacterial uptake, mast cell degranulation, gene expression and production of inflammatory mediators. Ct bacteria were taken up by mast cells but did not replicate efficiently inside CBMCs. Ct-activated mast cells did not degranulate but maintained viability and exhibited cellular activation with homotypic aggregation and upregulation of ICAM-1. Ct-treated mast cells significantly enhanced gene expression of IL1B, CCL3, NFKB1, CXCL8 and IL6. Inflammatory mediator proteins were produced, including TNF, IL-1β, IL-1RA, IL-6, GM-CSF, IL-23, CCL3, CCL5 and CXCL8. Endocytic blockade resulted in a reduction of gene expression of IL6, IL1B and CCL3 suggesting Ct-induced mast cell activation in both extracellular and intracellular locations. The role of pattern recognition receptors formyl peptide receptors and Toll-like receptor 2 (TLR2) were investigated using pharmacological inhibitors and soluble TLR2. The IL-6 response to Ct was reduced when CBMCs were treated with Ct coated with soluble TLR2. Mast cells derived from TLR2-deficient mice also demonstrated a reduced IL-6 response to Chlamydia muridarum. Mast cell-deficient mice and littermate controls were used to examine the in vivo role of mast cells in influencing the immune response to Chlamydia infection in the female reproductive tract. Five days following infection, during the acute phase, mast cell-deficient mice showed attenuated CXCL2 production and significantly reduced numbers of neutrophils, eosinophils, and B cells in the reproductive tract when compared with mast cell-containing littermates. Taken together, these data demonstrate that mast cells are reactive to Chlamydia spp. and play an important role in shaping immune responses in Chlamydia reproductive tract infection through both effector cell recruitment and modification of the cytokine microenvironment.